KARAKTERISASI DAN SIMULASI DIODA PN MEMPERGUNAKAN ALAT UJI OTOMATIS BERBASIS MIKROKONTROLER ATMEGA8A - Oktavia, Dian Putri; Hamzah, Yanuar; Umar, Lazuardi (Komunikasi Fisika Indonesia, 2016)
An automated test platform for I-U curve diode characterisation based on microcontroller of Atmega8A is presented. Four types of diodes; 1N4007, 1N5401, 1N5392, and 1N4148 were characterized at temperature 303K using step voltage (dU) of 1mV, 5mV, 10mV, 20mV, 50mV, 100mV, and 500mv respectively. The temperature influences on diode was observed by putting diodes in adiabatic temperature chamber at three different temperatures of 313K, 323K, and 333K, the I-U curve of diodes are then measured. The results show an exponentially diodes I-U curve at quadrant I (forward bias region). For diode parameters, the I-U curve were then modeled and simulated after diodes equation and resulted an maximum absolute error 10.57% of full scale measurement